2008
DOI: 10.2478/v10078-008-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sodium Phosphate Supplementation on VO2max, Serum 2,3-diphosphoglycerate Level and Heart Rate in Off-road Cyclists

Abstract: The main objective of the work was to evaluate the influence of a six day supplementation with sodium phosphate on circulatory and pulmonary variables, the level of 2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Increased 2,3-DPG concentrations after SP supplementation has also been associated with improved aerobic metabolism, as evidenced by increases inVO 2 max , 13,23,24 with Czuba et al 13 reporting a moderate correlation between these two measures (r = 0.47, p = 0.01). However, improvement in exercise performance after SP supplementation has also not always been associated with changes in 2,3-DPG concentration, [12][13][14] with no significant differences found for this measure here.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Increased 2,3-DPG concentrations after SP supplementation has also been associated with improved aerobic metabolism, as evidenced by increases inVO 2 max , 13,23,24 with Czuba et al 13 reporting a moderate correlation between these two measures (r = 0.47, p = 0.01). However, improvement in exercise performance after SP supplementation has also not always been associated with changes in 2,3-DPG concentration, [12][13][14] with no significant differences found for this measure here.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous mechanisms have been proposed to explain the ergogenic effects of SP supplementation. Briefly, these are increases in (a) 2,3-Diphosphoglycerate (DPG) in red blood cells, promoting oxygen unloading from haemoglobin to the tissues; 14 (b) myocardial efficiency, which may increase stroke volume; 12 (c) hydrogen ion buffering ability; 14 (d) adenosine triphosphate (ATP) and phosphocreatine (PCr) resynthesis due to a larger energy (phosphate) pool; 14 and (e) activation of rate-limiting constituents of the glycolytic and Krebs cycles. 15 Of relevance, all these mechanisms may potentially result in improved RSA, but this has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, best sprints were 0.13-0.23 and 0.15-0.20 s faster (~6 % improvement; p < 0.01) after SP compared with placebo and BJ, respectively, for all sets (d = −0.54 to −0.89). While some studies have found no benefit of SP on exercise performance (Brennan and Connolly 2001;Buck et al 2014;Brewer et al 2014;West et al 2012), others have reported improved endurance exercise performance (Folland et al 2008;Kreider et al 1992) and aerobic capacity of 3.5-12 % (Brewer et al 2013;Cade et al 1984;Czuba et al 2008Czuba et al , 2009Kreider et al 1990Kreider et al , 1992Stewart et al 1990) following 3.6-4 g or 50 mg kg −1 of fat free mass (FFM) of SP ingested each day over a 3-to 6-day loading period. Furthermore, Brewer et al (2014) recently reported improved sprinting and time-trial efforts whilst cycling following SP loading.…”
Section: Introductionmentioning
confidence: 99%
“…En el ejercicio físico, estas sales juegan un rol muy importante, ya que están involucradas en los tres sistemas de obtención de la energía. Los fosfatos forman parte del ATP y la fosfocreatina (CP), que son los sustratos básicos en los sistemas de fosfágenos de alta energía; también están involucrados en la glucólisis anaeróbica, amortiguando el efecto del ácido láctico producido en ejercicios de resistencia a la velocidad y participan activamente en el sistema de obtención de la energía por vía aeróbica (Czuba, Zając, Poprzecki y Cholewa, 2008;Williams, 1998). Kreider, Miller, Williams, Somma y Nasser (1990) examinan diferentes hipótesis por las cuales los suplementos de fosfato en deportistas podrían afectar el rendimiento.…”
Section: Introductionunclassified